The determinants of ecological footprint in the UK: The role of transportation activities, renewable energy, trade openness, and globalization - Eweade, Babatunde S.; Gungor, Hasan; Karlilar, Selin (Springer Heidelberg, 2023)
The objective of this study is to explore the interaction between transportation energy consumption, GDP, renewable energy, trade, globalization and ecological footprint in the United Kingdom over the period 1990-2020. To achieve this aim, the study uses the autoregressive distributed lag (ARDL) approach and Fourier Toda-Yamamoto causality test. The research findings demonstrate that an increase in transportation energy consumption, renewable energy, and globalization is associated with a reduction in environmental pollution. On the contrary, GDP and trade contribute to worsening the environment. Moreover, there exists a unidirectional causal relationship from transportation energy consumption, GDP, renewable energy, trade, and globalization towards the ecological footprint. The findings of the study recommend that the policymakers should implement strategies and provide incentives to increase the deployment of renewables in the transportation sector, specifically focusing on electric vehicles (EVs) and the necessary charging infrastructure. Overall, the UK government should prioritize sustainable environmental development when planning its economic development strategies.
Keywords: Transportation energy consumption; Renewable energy; Globalization; Trade openness; Economic growth; Ecological footprint; United Kingdom